Exploring college student's menstruation-related difficulties during early COVID-19 lockdown period in North India - Surbhi G Garg; Ruqayya Alvi; Suman Gupta; Absar Ahmad (Wolters Kluwer Medknow Publications, 2020)
Objective: Sanitary napkins are an essential aspect of the menstrual hygiene management. Despite its critical importance to women and adolescent girls from menarche and menopause, access to menstrual hygiene products has been neglected during the COVID-19 pandemic. At the time of this writing, there was no information on the challenges associated with accessing menstrual hygiene products in Indian settings during this period. This paper investigates the prevalence of socio-demographic correlations of access to sanitary napkins among college students in Lucknow, the largest state located in North India. Methods: Students of undergraduate (UG) and post-graduate (PG) courses currently studying in colleges in Lucknow were eligible to participate in the study. An online cross-sectional survey was conducted in Lucknow in September 2020. In total, 1439 participants took part in the survey. After removing 55 participants who quit the survey by clicking on the disagree button and 13 who did not satisfy inclusion criteria, the final sample comprised 1371 participants. The data collection was anonymous. Responses were analysed using descriptive statistics and bivariate logistic regression. Results: Up to 1371 students completed the survey, resulting in a response rate of 96.2 percent. The analysis revealed that about 12.5 percent of students reported problems in access to sanitary pads during the lockdown. Logistic regression analysis showed that being Muslim, having less-educated fathers, having farmers as fathers, having low income, rural residence, and a history of using cloth, all independently predict challenges in getting access to sanitary pads during the COVID-19 lockdown (P < 0.05). Conclusion: During the COVID-19 lockdown, students were dependent on either locally available resources as absorbents during menstruation or paid more to buy sanitary pads in Lucknow. Low-income families are reluctant to spend on sanitary pads, which is why few college girls resumed their previous practice of managing their periods using cloth pieces or rags. This study's findings may be used to plan and implement interventions during a future pandemic or such crises to maintain the supply chain of sanitary pad.